MENINGKATKAN KECEPATAN LARI 100 M DENGAN LATIHAN INTERVAL 1 BANDING 2 DAN 1 BANDING 3 (Jurnal Pedagogik Olahraga, 2016)
The purpose of this study is to know about the difference 1 to 2 with 1 to 3 the running speed of 100 meters, The method used is experimental pre-test and post-test group. The sample in this study uses total sampling is take the entire study population totaled 20 athletes. Treatments were used is interval training 1-to-2 and 1-to-3 a total of 16 times over the past 6 weeks, the practice is done 3 times each week. The variables of this study consisted oftwo independent variables is 1-to-2 interval training and interval training 1-to-3, dependent variable isSpeed of 100 meters. Instrument tests using whistle to cue, and stopwatch to measure the time taken. The data analysis techniques statistics using the t test with a significance level of 5%. Get results obtained indicate that the average speed (6,81m/s), and after the exercise program given intervals of 1 to 2 the average speed obtained (7,37m/s), and from the pre-test and post-test indicates that the after a given sample interval training program 1 to 2 increased speed of (0,56m/s). average running speed on the training sample intervals 1 to 3 before being given an exercise program (6,82m/s), and after the exercise program given intervals of 1 to 3 the average speed obtained (7,03m/s), and from the pre-test and post-test showed that after a given sample interval training program 1 to 3 increased speed of (0,21m/s). It can be concluded exercise intervals of 1 to 2 is better in improving the speed of the interval training 1-to-3 is 0,56>0,21. Keywords : Interval training ; Speed of 100 meters